Implementation of Freedom of Learning in Higher Education - Rajaminsah; Pian Supriatna Sulaeman; Saepul Kurniawan; Asan Azhari (al-Afkar, Journal For Islamic Studies, 2024)
The curriculum in Indonesia has undergone development. Today, the Independent Curriculum has emerged as an improvement and development of the 2013 curriculum. This policy certainly creates new concepts in the world of education, especially in higher education. Independent learning, the independent campus focuses on characteristic assessment to instill the values of Pancasila and diversity in diversity which are the hallmarks of the Indonesian nation. This article aims to explain the concept of an independent curriculum policy in higher education. The method used in this research is library research by collecting data from papers, journals, books related to the independent curriculum policy in tertiary institutions. The focus of this article is 1) the independent learning curriculum policy in higher education, the goals of independent learning in higher education 2) the independent learning program in higher education. The results of this study are adapting the independent learning policy, independent campus includes planning, learning process, assessment, and evaluation of learning. The independent learning curriculum emphasizes the process of learning activities outside and inside the campus.